2018
DOI: 10.1136/oemed-2018-105234
|View full text |Cite
|
Sign up to set email alerts
|

Risk of asthma and chronic obstructive pulmonary disease in a large historical cohort of Danish firefighters

Abstract: ObjectiveFirefighters are exposed to numerous respiratory hazards, but large studies on the risk of pulmonary disease are scarce. The objective of this study was to examine incidence of asthma and chronic obstructive pulmonary disease (COPD) in a nationwide cohort of Danish firefighters.MethodsWe used individual historical employment records on 11 968 Danish male firefighters primarily supplied by trade unions and fire agencies. Furthermore, we used the Supplementary Pension Fund Register to form an occupation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
3
16
2
Order By: Relevance
“…Firefighting is a dangerous profession that has the potential for both short-and long-term health consequences, such as cancer and respiratory diseases. [13][14][15][16][17][18][19][20][21][22] Firefighters exposed to the WTC disaster may have substantially greater risks of these and other health conditions. 12,25 population for WTC-exposed firefighters so that health outcomes in WTC disaster-exposed workers can be evaluated, independent of firefighting exposures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firefighting is a dangerous profession that has the potential for both short-and long-term health consequences, such as cancer and respiratory diseases. [13][14][15][16][17][18][19][20][21][22] Firefighters exposed to the WTC disaster may have substantially greater risks of these and other health conditions. 12,25 population for WTC-exposed firefighters so that health outcomes in WTC disaster-exposed workers can be evaluated, independent of firefighting exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Firefighting has been associated with cancer and other health risks, such as asthma, because of the potential for inhalation and contact exposures to harmful substances. [13][14][15][16][17][18][19][20][21][22] Thus, firefighting exposures outside of work at the WTC site may confound studies of the association between WTC exposure and disease outcomes in WTCexposed firefighters. Conversely, hiring standards for firefighters require that applicants meet stringent health criteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population constitutes all seafarers with a permanent address in Denmark aged 18-65 years at the baseline of 2002 and 2012. As employees, including seafarers, are normally characterized by being healthier than the general population [21,22], an external occupation reference group, namely people working in agriculture, was used to reduce a potential healthy worker effect. The two cohorts of seafarers and farmers in 2002 and 2012 consisted of 56,216 and 42,000 individuals, respectively.…”
Section: Study and Reference Populationmentioning
confidence: 99%
“…Several studies have shown associations between firefighting and various negative health outcomes, including certain cancers, 1–5 cardiovascular disease, 6 lung disease (ie, asthma), 7 and infertility 8 . As modern firefighters only spend approximately 0.75% to 2.7% of their professional time per year extinguishing fires, 9 it is not obvious how or if firefighting per se affects the risk of these diseases.…”
Section: Introductionmentioning
confidence: 99%